In Vitro Cercaricidal Activity, Acute Toxicity, and GC/MS Analysis of Some Selected Ghanaian Medicinal Plants - Bright Osei-Mensah; Yaw Duah Boakye; William Kofi Anyan; Theresa Appiah Agana; Eugene Agyei Aboagye; Ivy Bentil; Elvis Suatey Lomotey; Francis Adu; Christian Agyare (Journal of Parasitology Research)
Schistosomiasis is a human parasitic disease caused by the Schistosoma species and is recognised in public health as second to malaria in terms of its socioeconomic impact on humans. Four local plants native to many tribes in Ghana and known for their medicinal properties against some diseases were assessed for their cercaricidal activity against Schistosoma mansoni cercariae. The plants, namely, Newbouldia laevis stem bark (NLSB), Spathodea campanulata stem bark (SCSB), Momordica charantia leaves (MCL), and Ocimum viride leaves (OVL), were extracted for their active metabolites using methanol. Preliminary phytochemical screening was carried out on all plant extracts and powdered samples. The crude extracts were tested against S. mansoni cercariae in vitro using Balanites aegyptiaca as the positive control. The percentage of mortalities for each extract was recorded. Gas chromatography/mass spectrometry (GC/MS) analysis was conducted on all the plant extracts. Phytochemical analysis revealed the presence of saponins, glycosides, triterpenoids, sterols, alkaloids, flavonoids, and tannins in almost all the extracts. GC/MS analysis showed the presence of medicinally important active volatile compounds in each extract such as thymol, n-hexadecanoic acid, phytol, and maltol. All four plants showed relatively different levels of activity against S. mansoni cercariae at different times and concentrations. The LC50 values of the plant extracts were determined at the end of the assay. At 240 min, NLSB, SCSB, MCL, and OVL extracts had LC50 values of 487.564, 429.898, 197.696, and 0.129 μg/mL, respectively. Hence, this study revealed the potency of Ocimum viride leaves, Momordica charantia leaves, Spathodea campanulata stem bark, and Newbouldia laevis stem bark against S. mansoni. These plants could therefore be exploited as possible candidates for curbing schistosomiasis.